Association of Circulating Matrix Metalloproteinase-9 and the Risk of Coronary Heart Disease in Young Smokers - Nath, Dinesh; Shivasekar, Meera; Vinodhini, V.M. (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: Smoking causes cardiovascular risk which may alter the stability between the production and degradation of the extracellular matrix. Matrix metalloproteinase-9 (MMP-9) is a zinc-containing endopeptidase that degrades the extracellular matrix and plays a vital role in tissue remodeling. As a result, elevated serum MMP-9 levels produced by smoking, particularly at young age, raise the risk of future CHD. So this study aims to find out the possible relationship between circulating MMP-9 and the risk of cardiovascular disease in young smokers. Methods: The study was conducted on smokers with CHD subjects attending cardiology and medicine OP of the SRM Medical College Hospital and research center Tamil Nadu, India. The study group was divided into three groups. Group 1 includes 120 healthy controls as nonsmokers, Group 2 includes 120 smokers with Coronary heart disease (CHD), and Group 3 includes 120 smokers with diabetes and CHD subjects in the age group of 20-55 years. Serum MMP-9, hs-CRP, and APO-E levels were measured using the ELISA method and the lipid level was measured enzymatically using AU480 automatic analyzer (back man coulter). Results: The mean serum MMP-9, hs-CRP, and APO-E levels were significantly higher in both groups (p<0.05) when compared to controls. The study also shows a significant positive association between MMP-9 with hs-CRP, APO-E, smoking burden, and smoking intensity. Conclusion: The study concludes a significant association exists between cigarette smoking with MMP-9 and also relative exposure to circulating inflammation markers plays a potential role in the pathogenesis of CHD.